2014
DOI: 10.1002/acn3.154
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐Search: A web‐based therapy that improves visual search in hemianopia

Abstract: Persisting hemianopia frequently complicates lesions of the posterior cerebral hemispheres, leaving patients impaired on a range of key activities of daily living. Practice-based therapies designed to induce compensatory eye movements can improve hemianopic patients' visual function, but are not readily available. We used a web-based therapy (Eye-Search) that retrains visual search saccades into patients' blind hemifield. A group of 78 suitable hemianopic patients took part. After therapy (800 trials over 11 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…In this small sample study, they concluded that home‐based training is a feasible option and that the key factors for maximizing intervention potential include levels of cognitive impairment and participant perceptions. Free web‐based therapies are widely available in the form of Eye‐search (http://www.eyesearch.ucl.ac.uk) and Read‐right (http://www.readright.ucl.ac.uk), and their development has improved access to compensatory therapies for stroke survivors with visual field loss (Ong et al., 2012, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this small sample study, they concluded that home‐based training is a feasible option and that the key factors for maximizing intervention potential include levels of cognitive impairment and participant perceptions. Free web‐based therapies are widely available in the form of Eye‐search (http://www.eyesearch.ucl.ac.uk) and Read‐right (http://www.readright.ucl.ac.uk), and their development has improved access to compensatory therapies for stroke survivors with visual field loss (Ong et al., 2012, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have specifically reported on subjective improvements in activities of daily living following compensatory therapy, such as improvements in mobility, reading, driving, and detection of obstacles (Bergsma et al., 2011; Ong et al., 2015; Keller & Lefin‐Rank, 2010; Aimola et al., 2014; Jacquin‐Courtois et al., 2013; Kerkhoff et al., 1994; Mazer et al., 2003; de Haan, Melis‐Dankers, Brouwer, Tucha, & Heutink, 2015; Hayes, Chen, Clarke, & Thompson, 2012; Nelles et al., 2001; Rowe, Conroy, et al., 2016). A study by de Haan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Hemianopia A diagnosis of hemianopia was based on the results of a participants' visual field test (VFT). This test has been previously reported (Ong et al, 2015) and comprises a grid of 16 points (8 in each hemifield, two each at 1, 2.5, 5 and 10 degrees eccentricity). VFT over three time points (baseline, T1 and T2) were assessed to make sure that participants had consistent field loss.…”
Section: Study Definitionsmentioning
confidence: 99%
“…Eye-movement therapies have also been shown to be effective in treating the symptoms of neglect, although these rely on stimuli that induce smoothpursuit eye movements (e.g., patients have to focus on targets that move towards their neglected side at a constant velocity (Hopfner et al, 2015;Kerkhoff et al, 2014)). We have previously reported on the clinical efficiency of Eye-Search (https://www.eyesearch.ucl.ac.uk/), a web-based therapy that improves visual search in patients with hemianopia, but in that study (n = 78) we left out patients with neglect (Ong et al, 2015). As hemianopia and neglect can co-occur (Muller-Oehring et al, 2003), the aim of this study was to investigate whether Eye-Search therapy works in patients with either neglect alone ("pure neglect" group) or hemianopia and neglect.…”
Section: Introductionmentioning
confidence: 99%
“…Most modern training tools designed for this purpose are based on actively searching for digital targets displayed on a screen (e.g. Aimola et al, 2014; Ong et al, 2015; Sahraie, Smania, and Zihl, 2016; Chesham et al, 2019). Currently studies are also focusing on developing training protocols to improve visual search skills in children with visual field impairments arising from perinatal and acquired brain injury (Waddington and Hodgson, 2017; Ivanov et al, 2018; Waddington et al, 2018), or as a consequence of surgical interventions to treat other conditions such as hemi-disconnection surgery to treat intractable epilepsy (Koenraads et al 2014).…”
Section: Introductionmentioning
confidence: 99%